Spiritualitas Islam dalam Kewirausahaan - Hanifiyah Yuliatul Hijriah (TSAQAFAH, 2016)
Islamic spirituality refers to a paradigm of unity in realizing a harmonious balance between aspects of the world and the hereafter. This is an important aspect in fostering the forces that accompanied the faith toward Allah SWT, the power over all aspects of life, including for entrepreneurial activity. Islamic spirituality was born from every human which is capable of being utilized a strength in the form of spiritual intelligence. This element exists in every human being as grace of Allah SWT, which is useful for the activity of life. Results found that there were seven spiritual intelligence elements according to the Islamic perspective, there are: the faith, taqwâ, morality, ṣiddîq, amânah, tablîgh, faṭânah, discipline, visionary, and empathy. This qualitative study examines aspects of the spirituality of Islam containing potential elements in the form of spiritual intelligence that was potential for Islamic entrepreneurship in achieving sustainability of the business. The ability of businessmen to manage businesses, through attitude and decision making can be dependent upon the elements of the intelligence of Islamic spirituality. Islamic spiritual intelligence is able to be implemented in the business activities in order to achieve the sustainability of business, namely at the stage of production management, marketing, capital and human resources, where the result can be synergized to form a continuity of effort appropriate to The Islamic perspective. The orientation of the sustainability of the effort according to Islam was not only profit achievement, but also to achieve spiritual benefit that is also Allah SWT’s blessings.